Video and Film Editing Training for Literacy Activist at Home Reading Kali Atas, Cicalengka - Trias Pyrenia Iskandar; Charisma Asri Fitrananda; Yogi Mochamad Yusuf; Rasman Sonjaya (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
Videos and movies can be categorized as one of mass media in conveying messages to society. One of the important processes in video or film making is the editing process.The community service reported in this paper aimed to provide a training on film and video editing for literacy activists at the Kali Atas Community House of Reading, Cicalengka. Based on the analysis of the conditions faced by the participants, it was decided that the community service program should not only focus on increasing people's reading interest, but should also include activities that support the creativity of the community. The specific target expected from the training was to increase the participants’ creativity demonstrated by their ability to create video content that can attract people's reading interest. The film and video editing training was implemented for 3 weeks, starting from surveys, interviews, activities, evaluations, to final report. As a result of this activity, literacy activists who belonged to the Kali Atas Community House of Reading, Cicalengka, showed that they were able to produce a video that contained useful information for literacy promotion activities and this video was later uploaded on social media such as YouTube, Facebook, and Iinstagram. We recommend that this activity be continued to support literacy activities in Cicalengka such as discussion on media literacy, mural painting as well as more advanced training on film/video editing.